Screening for Cancer in Low- and Middle-Income Countries - R. Sankaranarayanan (Ubiquity Press, 2014)
Background: Screening programs involve testing asymptomatic individuals with an accurate screening test to identify those likely to have the disease of interest and to further investigate them to confirm or exclude the disease. The aim of cancer screening is to prevent cancer deaths and improve quality of life by finding cancers early and by effectively treating them. A decision to introduce a screening program in public health services depends on the evidence that the benefits outweigh the harms of screening, disease burden, availability of suitable screening test, effective treatment, adequate resources, and efficient health services. Screening programs should achieve high participation for testing, diagnosis, and treatment to be effective and efficient. Objective: To describe the current status of cancer screening programs in low- and middle-income countries (LMICs). Method: A review of literature and on-going cancer screening initiatives in LMICs was made to discuss cancer screening in these countries. Findings: Although population-based programs offering Papanicolaou testing every 3 to 5 years have reduced cervical cancer incidence and mortality in high-income countries, such programs have been less successful in reducing cervical cancer burden in LMICs due to poor organization, lack of coverage, and lack of quality assurance. The challenges in introducing high-quality cytology screening in LMICs have led to evaluation of alternative screening approaches such as visual inspection with acetic acid (VIA), human papillomavirus (HPV) testing-based screening, and novel paradigms such as a "single-visit screen and treat" in which treatment with cryotherapy or cold coagulation is provided to screen-positive women without clinical evidence of cancer. Both HPV testing and VIA have been found to prevent cervical neoplasia and cervical cancer deaths in clinical trials. Although mammography screening reduces breast cancer mortality, associated overdiagnosis and overtreatment and the balance between benefits and harms have received much attention in recent years. Although introduction of clinical breast examination screening in LMICs should wait for evidence from ongoing trials, improving breast awareness and access to early diagnosis and treatment in health services is a valuable breast cancer control option in LMICs. Organized colorectal cancer screening programs are still evolving and are in early stages of development in many high-income countries. To date, there is insufficient evidence to support the introduction of population-based stomach, lung, ovarian, and prostate cancer screening in public health services. Conclusions: Implementation of VIA screening in several LMICs is conducive to future HPV screening programs when affordable HPV tests become widely available. Both HPV vaccination and HPV screening have a huge potential to eliminate cervical cancer in LMICs. A mammography screening program is a complex undertaking involving substantial resources and infrastructure that may not be feasible in many LMICs.